Smart Service Dimensions: Exploring Customer Experience and Participation using Stimulus-Organism-Response Model - Abdul Ghani, Nadiah Maisarah; Ariffin, Ahmad Azmi Mohd; Yunus, Nor Sara Nadia Muhamad; Mohd Salleh, Mohammad Zaim (Advances in Social Sciences Research Journal, 2023)
Today, the emergence of smart service technologies has an impact on customer experience and customer participation in the service industry. Artificial intelligence (AI) appears likely to influence marketing strategies, including business models, sales processes, and customer service options, as well as customer behaviors. Technology has been regarded as a game changer in the service context. As consumers become more accustomed to smart technology and robotic services, technology will continue to play an essential role in the service industry to better serve customers. While using smart technology, customers themselves will be involved in the service process. They will participate in the service with no or limited involvement with the staff. Therefore, it is very crucial to emphasis the technology-enhanced experience from a customers’ perspective to have better understanding of the actual content and operational application of smart service and robotic experience by examining the specific dimensions of the smart service. Therefore, this proposed study aims to provide an intense discussion and comprehensive conceptualization of the smart service dimensions that may stimulate customer experience and participation by using Stimulus-Organism-Response (S-O-R) Model.